Adapting violence for state survival and legitimacy: the resilience and dynamism of political repression in a democratizing South Korea*. Issue 4 (19th May 2019) - Kim, Sunil; Porteux, Jonson N.
ABSTRACT: Capacity in violence and its utilization is generally understood to be a first-order condition of the state-building process. As capacity increases and a state gains supremacy over would-be competitors, the use of violence by the state is hypothesized to decline, especially in polities that have made the democratic transition. However, we here demonstrate theoretically and empirically that the conventional wisdom is inadequate. We argue that political violence ubiquitously evolves according to the changing socio-political environment and varying tasks of the state. Using the case of South Korea, a high-capacity, consolidated democracy, as a prism for theory building and corroboration, this study chronicles the evolution of political violence from the state's explicit mobilization of thugs to suppress opposition at the early stage of state building through its collaboration with criminal organizations for developmental projects to the manipulation of quasi-governmental organizations after democratization in the late 1980s, coeval with the traditional use of public sources of force. We specifically look at how political development, that is, democratization, has produced new demands for – and constraints on – political violence and how post-authoritarian governments have responded.